(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge and practices related to hypertension management among outpatients at Saint Paul General Hospital in 2022. Methods: A cross-sectional descriptive study was conducted on 96 patients diagnosed with hypertension from February to May 2022 at the Outpatient Department of Saint Paul General Hospital. Results: The proportion of patients with adequate knowledge of hypertension management was 73.95%, while 63.5% demonstrated adequate practices. Although patients had good knowledge in several areas, some aspects remained limited, including maintaining a healthy weight and avoiding overweight/obesity (54.17%) and engaging in moderate physical labor (46.88%). Several practices were suboptimal, such as regular health check-ups every less than three months (36.46%), daily blood pressure monitoring (16.67%), exclusive use of vegetable oil (58.33%), engaging in physical exercise for 30–60 minutes per day (56.25%), and appropriate management of sudden blood pressure elevation (56.25%). Conclusion: The study found that 73.95% of patients had adequate knowledge and 63.5% had adequate practices regarding hypertension management. Patients still had limited knowledge regarding weight control and physical activity. A gap between knowledge and practice persists, with some patients showing inadequate behaviors in blood pressure monitoring, regular health check-ups, maintaining a healthy lifestyle, and managing sudden hypertension episodes. Therefore, health education interventions are needed to improve areas where patients’ knowledge and practices remain insufficient.